Influenza vaccination—acceptance in an industrial population. Issue 4 (October 1974) - Smith, J. W. G.; Pollard, R.; Fletcher, W. B.; Barker, R.; Lewis, J. R.
Abstract : Smith, J. W. G., Pollard, R., Fletcher, W. B., Barker, R., and Lewis, J. R. (1974). British Journal of Industrial Medicine, 31, 292-297. Influenza vaccination—acceptance in an industrial population. Influenza vaccination was offered in a pharmaceutical factory of approximately 6 000 employees in December 1971 and again in December 1972. The rate of acceptance of vaccination was 42% in 1971 but fell to only 27% in 1972, and was highest among middle-aged married women and lowest among young men. Only 57% of employees who were vaccinated in 1971 and were still employed in 1972 accepted vaccination on the second occasion. Re-vaccination was commoner in staff (64%) than in works employees (52%) in all age and sex categories, and was commoner in older than in younger employees. Only 6% of employees who did not accept vaccination in 1971 accepted the vaccine in 1972. Among new employees who were not in the factory in December 1971 the acceptance rate was 21% in 1972. Between January 1971 and 1972 vaccinated employees left the factory less commonly (15%) than those who had not accepted vaccination (22%). Loss of working time in April to September 1972, i.e., when it is unlikely that influenza would have influenced the returns, was 21% higher among non-vaccinated employees than in vaccinated employees, the difference being due to certified illness of more than three days' duration. The benefit to be derived from offering influenza vaccination to a factory or office population will depend, among other factors, on the proportion of employees who accept the offer and on the characteristics of this volunteers group. The low take-up rate (27%) observed in the second year suggests that annual influenza vaccination is unlikely at the present time to have a marked effect on absence during outbreak periods. In comparison with the non-volunteers in the present study, the volunteers included a higher proportion of married women, older persons, and staff employees and were less inclined to leave employment, and lost less working time from certificated sickness absence. The value of offering vaccine may therefore be greatest in an established office employing a high proportion of older women. The differences between the volunteers and non-volunteers, particularly the better sickness absence record of the former, indicates that the effect of influenza vaccination cannot reliably be assessed only from a comparison of absence returns between vaccinated and unvaccinated employees.